Monetary Instruments and their Use During the Transition From a Centrally Planned to a Market Economy - Hilbers, Paul (IMF Working Papers; Working Paper, 1993)
This paper discusses different instruments of monetary policy, and in particular the choice between direct and indirect instruments. It identifies the main characteristics of a country's financial system that should be considered in selecting monetary instruments, and analyzes how these characteristics should influence that selection in countries that are progressing from a state-controlled to a market economy. The characteristics of the financial system during the initial stage of the transition sometimes favor relatively direct instruments. At this stage market-based variants of direct instruments may combine the necessary effectiveness in reducing monetary expansion with the need to introduce and stimulate competition in the financial markets. During this stage indirect instruments can be developed and tested ('belt and braces' approach). In later stages, as experience is gained, these indirect instruments can gradually replace the more direct controls.